Success is for you : using heart-centered power principles for lasting abundance and fulfillment - Hawkins, David R., 1927- (Hay House, Inc., 2016)
"Success Is for You draws upon many concepts that fans of Dr. Hawkins will recognize and applies them to the world of business and the psychology of success. Expanding upon the illuminating discussion of the attractor patterns of success from Power vs. Force, this remarkable never-before-published book pulls back the curtain on the inner workings of the successful mind. Success, according to Dr. Hawkins, is an attitude we inhabit, rather than a goal we strive for. New readers will find this to be a perfect introduction to an incredible teacher and foremost expert on mental processes, providing profound insights and real-world examples to help anyone focus on--and consequently achieve--what they desire. This fascinating book reveals: · The causality formula for success (and deconstruction of so-called failure) · How goodwill can actually turn to profit · Nine acid-test steps to determine our mode of being · How to "get to the top" (and why the destination is really our starting point) Yet its scope ranges far beyond a mere how-to manual. As Dr. Hawkins says, "Having facts and know-how. does not guarantee success. There are other factors involved. It is these other secret factors that we are going to explore." The secret factors--the energetic power principles underlying success--are decoded here. delivering an eternal message of possibility for us all. "--